2013
DOI: 10.1103/physreva.87.043820
|View full text |Cite
|
Sign up to set email alerts
|

Blueshifted continuum peaks from filamentation in the anomalous dispersion regime

Abstract: International audienceFilamentation in the anomalous dispersion regime is experimentally shown to give rise to an extreme blueshifted continuum peak in the visible region even when the filament is formed by near-infrared pulses. Measurements and numerical simulations allow us to identify this peak as an axial component of the conical emission. Its features are characterized and quantitatively reproduced by the effective three-wave mixing model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 21 publications
5
28
0
Order By: Relevance
“…Similar RR emission predicted by the very same phase-matching relation, occurs in 3D both for pulses in the anomalous and normal GVD regimes [22,23]. For normal GVD pumping however, significant continuous spectral broadening may occur simultaneously and it is only for a pump in the anomalous GVD that the RR appears as an isolated spectral peak with strong similarities to the 1D soliton perturbation as observed in a variety of bulk media [20,24,25].…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Similar RR emission predicted by the very same phase-matching relation, occurs in 3D both for pulses in the anomalous and normal GVD regimes [22,23]. For normal GVD pumping however, significant continuous spectral broadening may occur simultaneously and it is only for a pump in the anomalous GVD that the RR appears as an isolated spectral peak with strong similarities to the 1D soliton perturbation as observed in a variety of bulk media [20,24,25].…”
supporting
confidence: 70%
“…Although such light bullets lend themselves to a tempting analogy with 1D fundamental solitons, recent work has shown that in fact 3D light bullets correspond to a form of polychromatic (weakly localised) Bessel beam that emerges spontaneously during the collapse phase of an initially Gaussian-shaped wavepacket [19]. Despite this difference, light bullets do exhibit remarkable similarities with 1D solitons: (i) they appear to propagate quasi-undistorted without pulse splitting as observed in the normal GVD regime; (ii) temporal compression may occur in a fashion similar to soliton compression and (iii) their propagation in the presence of higher-order dispersion perturbation is accompanied by the emission of a resonant radiation (RR) often referred to as a dispersive wave [18,20,21].In this letter, we report on the observation of optical rogue waves associated with the emission of extreme RR during the formation of 3D light bullets in a nonlinear crystal induced by the spatio-temporal coupling of fluctuations inherently present on the input beam. The deterministic spatio-temporal dynamics are central to the rogue characteristics of the RR emission as a result of the steep shock front that forms on the trailing edge of the pulse during the initial collapse phase and whose gradient is highly sensitive to fluctuations in both the input energy and spatial phase curvature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] demonstrate unexpected long light-bullet propagation and reveal also another interesting point. The propagation dynamics are accompanied by the generation of blueshifted radiation [28], a phenomenon which is observed also under different conditions [8,[29][30][31][32] even for short filament lengths.…”
mentioning
confidence: 82%
“…The angle-integrated as well as the axial SC spectra show an intense blue-shifted peak located in the visible range, which is identified as an axial component of the conical emission and whose blue-shift increases with increasing the wavelength of the driving pulse [157,158]. Various aspects of the spectral broadening and SC generation, such as energy content, stability of the carrier envelope phase, etc., were studied in connection with formation and propagation dynamics of spatiotemporal light bullets [77, 159, 3 μm laser pulse in a 3 mm-long fused silica sample versus the input pulse energy.…”
Section: ]mentioning
confidence: 99%